PHILIP MORRIS COMPANIES INC. FIVE YEAR PLAN 860000 - 900000 (Tufts Archival Research Center, 2007)
Document detailing the five year plan from Philip Morris to increase market share, net earnings and general revenue for the company. Outlines the goals to be achieved and the tactics to be employed in this endeavor.